2012
DOI: 10.1186/2049-1891-3-34
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenomics for identification of disease resistance genes in pigs: a review focusing on Gram-negative bacilli

Abstract: Over the past years, infectious disease has caused enormous economic loss in pig industry. Among the pathogens, gram negative bacteria not only cause inflammation, but also cause different diseases and make the pigs more susceptible to virus infection. Vaccination, medication and elimination of sick pigs are major strategies of controlling disease. Genetic methods, such as selection of disease resistance in the pig, have not been widely used. Recently, the completion of the porcine whole genome sequencing has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…However, performance and production traits are often highly complex and the outcome of agricultural operations is affected by variations at all levels. For example, genetic background is very important because disease resistance genes allow the organism to survive the serious infections [ 12 , 13 ]. In most cases, disease resistance genes have been studied through genetic linkage and QTL analyses that allow the identification of genomic regions containing disease resistance genes to be identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, performance and production traits are often highly complex and the outcome of agricultural operations is affected by variations at all levels. For example, genetic background is very important because disease resistance genes allow the organism to survive the serious infections [ 12 , 13 ]. In most cases, disease resistance genes have been studied through genetic linkage and QTL analyses that allow the identification of genomic regions containing disease resistance genes to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Even with the most powerful molecular approaches, analysis of complex traits such as disease resistance can be extremely challenging. In 1991, Michelmore et al developed a method called bulked segregant analysis (BSA) to study disease resistance in plants [ 13 - 20 ]. The basic idea of BSA was that phenotypic extremes should have drastic differences in genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…In the US, porcine reproductive and respiratory syndrome virus (PRRSV) alone costs swine producers millions of dollars per year (Brito et al, 2014). In China, the annually economic loss caused by infectious disease in the pig industry is estimated to be RMB 40 billion (equivalent to > $6Bn) (Zhao et al 2012). The main approaches for prevention and control of diseases include vaccination and medication, elimination of sick animals, the maintenance of high levels of bio-security, and all-in-all-out production.…”
mentioning
confidence: 99%
“…Recent research using these methods has identified critical candidate genes through gene network and pathway analysis in immune response experiments related to PRRSV resistance and gram-negative Bacillus resistance in pigs (Wysocki et al, 2012;Zhao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%